NMDA receptor-dependent long-term potentiation in mouse hippocampal interneurons shows a unique dependence on Ca(2+)/calmodulin-dependent kinases. - Lamsa, K; Irvine, E; Giese, K; Kullmann, D (2007)
Long-term potentiation (LTP) of excitatory synaptic transmission plays a major role in memory encoding in the cerebral cortex. It can be elicited at many synapses on principal cells, where it depends on Ca(2+) influx through postsynaptic N-methyl-D-aspartic acid (NMDA) receptors. Ca(2+) influx triggers phosphorylation of several kinases, in particular Ca(2+)/calmodulin-dependent kinase type II (CaMKII). Auto-phosphorylation of CaMKII is a key step in the LTP induction cascade, as revealed by the absence of LTP in hippocampal pyramidal neurons of alphaCaMKII T286A-mutant mice, where auto-phosphorylation of the alpha isoform at residue T286 is prevented. A subset of hippocampal interneurons mediating feed-forward inhibition also exhibit NMDA receptor-dependent LTP, which shows all the cardinal features of Hebbian LTP in pyramidal neurons. This is unexpected, because alphaCaMKII has not been detected in interneurons. Here we show that pathway-specific NMDA receptor-dependent LTP is intact in hippocampal inhibitory interneurons of alphaCaMKII T286A-mutant mice, although in pyramidal cells it is blocked. However, LTP in interneurons is blocked by broad-spectrum pharmacological inhibition of Ca(2+)/calmodulin-dependent kinases. The results suggest that non-alpha Ca(2+)/calmodulin-dependent kinases substitute for the alpha isoform in NMDA receptor-dependent LTP in interneurons.